Primary Schoolchildren’s Difficulties at School Following the Multiple Crises: A Single Center Cross-Sectional Study - Abdo, Hiba; Chehabeddine, Mouna; Chehabeddine, Hiba; Nasrallah, Inaam; El-Kak, Assem; Hatem, Georges (Educational Challenges, 2024)
Purpose. This study aims to evaluate schoolchildren's strengths and difficulties following crises. Methods. A pilot cross-sectional study was carried out over two months (April – May 2023) using a standardized questionnaire for data collection. A convenient sample of 130 students was recruited from a private school and included in this study. A comparison between groups was carried out on several factors: conduct problems, peer problems, emotional score, hyperactivity, and total difficulties scores. Bivariate analyses were conducted, in which the dependent variables were age, sex, and difficulty scores. Results. A significant risk for peer problems (32.2%) and emotional symptoms (22.2%) was noted among the participants. A substantial risk of clinically significant problems was associated with hyperactivity. Girls presented an increased risk of clinical problems (46.9%) associated with their emotional symptoms, significantly higher than males (25%; p=0.015), resulting in significantly more clinical problems associated with their total difficulties score compared to boys (32.3% versus 15.1%; p=0.031). Overall, most students (90.9%) had no significant problems. However, 5% had a slightly low prosocial scale, and 4.1% had lower scores, reflecting a high probability of substantial clinical risk. Conclusion. The crises in Lebanon have exacerbated existing inequalities in access to education, leading to or exacerbating school difficulties. Findings reflected the influence of parents and the school on the children’s academic performance and psychological well-being and highlighted the need for providing additional support to schools and investing in mental health services for students.